The Munakkid's Specific Style - Bektasheva Gulbahor Rayimjonovna (Genius Publishing Group, 2022)
This article provides an in-depth analysis of the scientific and creative activity of the literary critic B. Kasimov, both artistically and aesthetically, as well as sociophilosophically. The directions of the critic's analysis are given. It is said that the scholar studied the heritage of the Jadids on the basis of original sources and archival materials.
Keywords: Literary-aesthetic view; jadidism; aesthetic motive; hermeneutics